2012
DOI: 10.1021/cn300014e
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid Signaling in Female Reproduction

Abstract: Marijuana is a preparation of the flower, as well as the leaves and seeds, of the plant Cannabis sativa. Marijuana has been used for medicinal and recreational purposes for thousands of years due to its psychoactive effects including euphoria, sedation, and analgesia. Although it has been suspected for decades that marijuana has adverse effects on female fertility, the underlying molecular mechanism was not clear. The discovery of cannabinoid receptors and endocannabinoids has advanced studies if cannabinoid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 69 publications
(141 reference statements)
1
54
0
2
Order By: Relevance
“…The role of the endocannabinoid system has been studied in mammalian reproductive events, such as spermatogenesis, sperm motility, fertilization, embryo oviductal transport, preimplantation embryo development, implantation, and postimplantation embryonic growth (21)(22)(23). Even so, the role of this system in the ovary and oocyte events has rarely been analyzed (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the endocannabinoid system has been studied in mammalian reproductive events, such as spermatogenesis, sperm motility, fertilization, embryo oviductal transport, preimplantation embryo development, implantation, and postimplantation embryonic growth (21)(22)(23). Even so, the role of this system in the ovary and oocyte events has rarely been analyzed (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, higher anandamide levels inhibit blastocyst differentiation, oviductal transport, implantation and trophoblast proliferation. 23 Studies have shown that low FAAH and high CB1 expression in human placenta characterize spontaneous miscarriage, 24 whereas both low FAAH and CB1 expressions causing high anandamide levels in fallopian tubes may have a role in ectopic implantation. 25 High maternal peripheral blood endocannabinoid levels modulated by low FAAH activity in lymphocytes can inhibit successful pregnancy after in vitro fertilization, 26,27 and were recently associated with ectopic pregnancy possibly through tubal dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the endocannabinoid system has been studied in various mammalian reproductive processes, such as spermatogenesis, sperm motility, fertilization, embryo oviductal transport, preimplantation embryo development, implantation, and post-implantation embryonic growth (Wang et al 2006a(Wang et al , 2006bTaylor et al 2007;Sun and Dey 2012). Even so, the part played by this system in the ovary and in oocyte events has rarely been analyzed (El-Talatini et al 2009;Bagavandoss and Grimshaw 2010;Peralta et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Among these molecules, the role of the cannabinoid compounds has been highlighted by some authors (Sun and Dey 2012). Endocannabinoids are fatty acid derivatives that exert their effects by binding to membrane Gi/o protein-coupled receptors CB1 and CB2.…”
Section: Introductionmentioning
confidence: 99%